2017
DOI: 10.1007/s10530-017-1579-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying site-level usage and certainty of absence for an invasive species through occupancy analysis of camera-trap data

Abstract: Efficient implementation of management programs for invasive species depends on accurate surveillance for guiding prioritization of surveillance and control resources in space and time. Occupancy probabilities can be used to determine where surveillance should occur. Conversely, knowledge of the certainty of site-level absence is of special interest in situations where the objective is to completely remove populations despite substantial risk of reinvasion. Indeed, the decision to shift from emphasizing contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…We note that recent features on virtually all trail camera models include a burst of images when the camera is triggered, and the resulting series of images allows different views of individuals which may improve classification (Rovero, Zimmermann, Berzi, & Meek, ). Increasingly, burst or video settings (which would also provide multiple image angles) are being used in camera‐trapping studies and are quickly becoming standard practice among researchers (Comer et al, ; Davis et al, ; Hedwig et al, ; Ladle, Steenweg, Shepherd, & Boyce, ; McCarthy et al, ). Likewise, Gooliaff and Hodges note that the use of multiple images may result in an improved classification, but this added realism was not included in their analysis.…”
mentioning
confidence: 99%
“…We note that recent features on virtually all trail camera models include a burst of images when the camera is triggered, and the resulting series of images allows different views of individuals which may improve classification (Rovero, Zimmermann, Berzi, & Meek, ). Increasingly, burst or video settings (which would also provide multiple image angles) are being used in camera‐trapping studies and are quickly becoming standard practice among researchers (Comer et al, ; Davis et al, ; Hedwig et al, ; Ladle, Steenweg, Shepherd, & Boyce, ; McCarthy et al, ). Likewise, Gooliaff and Hodges note that the use of multiple images may result in an improved classification, but this added realism was not included in their analysis.…”
mentioning
confidence: 99%
“…We 334 examined two levels of uncertainty in abundance (Uo: low and high). We assumed that the 335 process for observing abundance is biased low (underestimation of the true abundance) 336 because studies that have estimated detection probability during management-based monitoring 337 in populations have found that it is well below 1 (e.g., (Davis et al 2018b), although in the 338 supplementary information we also present results for instances where abundance estimation is 339 imperfect but unbiased; Appendix 1: Fig. S10).…”
Section: Observational Uncertainty In Abundance 330mentioning
confidence: 99%
“…Even when detection is highly reliable, it is inefficient to survey everywhere across all areas at risk with the same degree of effort, since invasions rarely progress across a landscape in uniform fashion [39,41]. Moreover, surveillance is merely one element of post-border response to invasions; regularly, decision-makers must assess the trade-offs of devoting limited resources to surveillance instead of other management efforts [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%